Preparation and Superficial Characteristics of Light-Cured Resin Containing Negative Ion Powder. Issue 5 (June 2019) - Zhu, Jingli; Ding, Lili; Shi, Jiatong; Liu, Bin
Abstract: The objective of this paper is to prepare light-cured resin material containing negative ion powder, test and evaluate the performance of its composite material, and provide some experimental basis for its clinical application. Adopt mechanical agitation dispersion and ultrasonic dispersion for ultra-fine processing of negative ion powder. Prepare the antibacterial composite resin by evenly dispersing negative ion powder in 4% ratio of 0% to 2% in Durafill composite resin. Observe the dispersion uniformity of antimicrobial agents by scanning electron microscope (SEM), and use Fourier transform infrared spectroscopy (FTIR) to determine the curing rate of the modified composite resin after adding different proportion of negative ion powder. Test the microhardness of modified composite resin by Vickers microhardness meter. The SEM result shows that the negative ion powder was dispersed uniformly in the composite resin. The results of initial curing rate of composite resin showed that the addition of negative ion powder did not lead to the decrease of curing rate but increased the curing rate to some extent. The mechanical properties test showed that the surface hardness was decreased compared with the control group, and it was gradually decreased with the increase of the proportion of negative ion powder.